Design and implementation of multi-kW and multi-MHz gallium nitride full-bridge inverter for high-frequency wireless power transfer system - Ning, Jianping (Nanyang Technological University, 2025)
Wireless power transfer (WPT) systems benefit from enhanced efficiency, reduced size, and extended transmission distance when operated at MHz frequencies. This study presents the design and implementation of a high-power full-bridge inverter employing gallium nitride (GaN) devices, which are characterized by low conduction losses, high switching speed, and elevated power density. The inverter is optimized for operation at 6.78 MHz, targeting high-efficiency WPT applications. Experimental results validate the system’s stable performance under variable load conditions, achieving a peak efficiency of 92.88% at an output power of 872.3W with a 250V input, and 91.80% at 2180W with a 400V input. Key performance indicators, including the realization of zero-voltage switching (ZVS) and favorable thermal characteristics, substantiate the suitability of GaN devices for MHz-range power conversion. These findings highlight the advantages of GaN-based inverters over traditional silicon counterparts in terms of both efficiency and power density.